CODE MIXING AS A FORM OF INDONESIAN IDENTITY BASED ON THE MOTTO OF BHINNEKA TUNGGAL IKA - Nugraha, Fajar Muhammad (UI Scholars Hub, 2019)
In 2018, the Language Comission of the Ministry of Education and Culture (Kemendikbud) of the Republic of Indonesia has made verification towards all the languages that exists in Indonesia. The verification conducted from 1991 to 2017 resulted in 652 languages to be found. That number still does not include the dialects and their sub-divisions of the 652 languages. Meanwhile, UNESCO recorded 143 languages based on their vitality status. Identity can be interpreted as similarity or unity with others in a certain area or other things (Rummens, 1993: 157-159).